A MULTI-CRITERIA EVALUATION OF THE EUROPEAN CITIES’ SMART PERFORMANCE: ECONOMIC, SOCIAL AND ENVIRONMENTAL ASPECTS - Stanković, Jelena; Džunić, Marija; Džunić, Željko; Marinković, Srđan (Zbornik radova Ekonomskog fakulteta u Rijeci, 2017)
The purpose of the paper is to provide the ranking of Central and Eastern European cities, based on various elements of cities' smart performance. Our analysis enables the evaluation of social, economic and environmental aspects of urban life that represent the determinants of cities' competitive profiles and consequently, the positions on the ranking lists. The research is based on the data on perceptions of citizens on different aspects of urban quality, provided by the Eurostat's Urban Audit Perception Survey. For the assessment of various hierarchically structured indicators of cities' smart performance, a multi-criteria analysis model is developed, combining the AHP (Analytic Hierarchy Process) for determining the relative importance of criteria and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method of ranking. The main finding of the paper implies that direct perceptions of citizens on the overall life satisfaction in the analyzed European cities are not influenced by their smart performance. The comparison of ranks obtained by the constructed multi-criteria model and perceived satisfaction of life indicates a rather weak relation.